How to understand financial statements : a nontechnical guide for financial analysts, managers, and executives / [disket] - 303847 Ferris, Kenneth R.; Tennant, Kirk L.; Jerris, Scott I. (Englewood Cliffs, N.J. : Prentice Hall, 1992)
System requirements: IBM or compatible, 286 or higher.